Mitigating Interoperability and Integration Hurdles in Cloud Computing Implementation: A Professional Perspective - Mahesh Prabu Arunachalam (International Journal of Engineering and Management Research, 2024)
Cloud computing is an option for organizations that do not intend to invest in internal IT resources. It offers a service model that assumes that the consumer has the means to manipulate information on the Internet according to their current needs. However, IT outsourcing presents various challenges, such as effective IT management, attention to threats from the Internet ecosystem, and concerns about efficient use of resources. Thus, the uncertainty associated with the transition to cloud computing can have a negative impact on the adoption of this technology. To better inform the decision-making process of organizations considering cloud computing, this study presents a literature-based list of key questions that can help IT managers guide an organization toward effective and secure adoption of cloud computing solutions. In addition, interviews were conducted with IT managers of companies using and providing cloud services to understand and prioritize these issues. The list takes into account the views of operators who have successfully experienced the transition to the cloud environment.